An investigation into the effect of eight weeks of aerobic exercise with orange juice consumption on antioxidant capacity and inflammatory factors in overweight middle-aged women - Sadat Ghalishourani, Samira; Abed Natanzi, Hossein; Ansari, Samaneh; Baghdadi, Ghazal; Feyzpour, Marzieh (Researcher Bulletin of Medical Sciences, 2025)
Objective: Overweight and obesity are among the most important public health concerns associated with several negative health outcomes. Several studies have found that the positive impact of orange juice may be due to the presence of its antioxidants, especially flavonoids and vitamin C. Vitamin C as an antioxidant is capable of neutralizing water-soluble ROS. Therefore, this study aimed to investigate the effect of eight weeks of aerobic exercise with orange juice extract on antioxidant capacity and inflammatory factors in overweight women. Materials and Methods: A total of 60 overweight women participated in this study voluntarily. The research sample was selected using a random sampling method. They were then randomly divided into 4 groups. The treadmill endurance training protocol was carried out with a run-walk program for eight weeks, three sessions per week. All data were then entered into SPSS 24 to be analyzed. Results: The results obtained by this study showed that eight weeks of aerobic exercise with orange juice consumption had no significant effect on high-sensitivity C-reactive protein (hs-CRP) levels and total antioxidant capacity in overweight middle-aged women, but eight weeks of aerobic exercise with orange juice consumption had a significant effect on malondialdehyde (MDA) levels and VO2max amount in overweight middle-aged women (P= 0.001). Conclusion: Statistical studies showed that eight weeks of aerobic exercise with orange juice consumption causes a reduction in MDA levels, and orange juice consumption combined with aerobic exercise can have a synergistic effect compared to aerobic exercise alone and increase the effect of exercise on the oxidative stress suppression